Наукова дипломатія та зовнішня політика: протидія глобальним викликам і загрозам - Марутян Рена (My University, 2022)
In the chapter, based on a systemic approach, science diplomacy is investigated as a component of modern foreign policy, which becomes an effective mechanism for countering global challenges and threats. The purpose. The purpose of the study is a theoretical analysis of the essence and tools of scientific diplomacy and, on this basis, the development of a proposal for the development of scientific diplomacy in Ukraine. Methodology. The methodological basis of the research consists of such methods of scientific knowledge as analysis, inductive and deductive, comparison, generalization, synthesis and forecasting. Results. The research proved that the globalization of the world and the emergence of modern challenges and threats require the combined efforts of diplomats and scientists. In the knowledge society, the scientist becomes an important actor in international relations, whose activity is decisive in overcoming local and global crises, including pandemics and regional military conflicts. The current foreign policy situation requires the institutional consolidation of scientific diplomacy as a mechanism for ensuring Ukraine’s foreign policy security. Value/originality. The originality of the research lies in the fact that the author proposed proposals for the development of scientific diplomacy in Ukraine.

У розділі на основі системного підходу досліджено наукову дипломатію як складову сучасної зовнішньої політики, яка стає ефективним механізмом протидії глобальним викликам і загрозам. Метою дослідження є теоретичний аналіз сутності та інструментів наукової дипломатії та на цій основі розробка пропозиції щодо розвитку наукової дипломатії в Україні. Методологічну основу дослідження становлять такі методи наукового пізнання, як аналіз, індуктивний та дедуктивний, порівняння, узагальнення, синтез та прогнозування. У процесі дослідження доведено, що глобалізація світу та поява сучасних викликів і загроз потребують об’єднання зусиль дипломатів і науковців. У суспільстві знань науковець стає важливим актором міжнародних відносин, діяльність якого є вирішальною в подоланні локальних і глобальних криз, включаючи пандемії та регіональні військові конфлікти. Сучасна зовнішньополітична ситуація потребує інституційного закріплення наукової дипломатії як механізму забезпечення зовнішньополітичної безпеки України. Оригінальність дослідження полягає в тому, що авторка зробила пропозиції щодо розвитку наукової дипломатії в Україні.

Розділ 3.8. колективної монографії «Глобалізаційні виклики: урядування майбутнього».